The combined effect of pomegranate extract and tangeretin on the DMBA-induced breast cancer model - Gul, Huseyin Fatih; Ilhan, Necip; Ilhan, Nevin; Ozercan, Ibrahim Hanifi; Kuloglu, Tuncay (Elsevier Science Inc, 2021)
The aim of this study was to investigate the protective effects of pomegranate extract and tangeretin alone or in combination in DMBA-induced rat breast cancer model. A total of 68 female rats were randomly divided into 8 groups. The first 4 groups were designed as controls for cancer and treatment groups, and the control groups were composed of only control (C), Pomegranate (P), Tangeretin (T), and Pomegranate +Tangeretin (P + T) groups. The other four groups were designed as cancer and treatment groups and were composed of DMBA (D) and DMBA + Pomegranate (D + P), DMBA +Tangeretin (D + T), DMBA + Pomegranate +Tangeretin (D + P + T) groups. Tumor markers and angiogenesis parameters were studied from plasma samples obtained from rats. Histopathological, immunohistochemical, and TUNEL analyses and expressions of proteins affecting apoptosis and cell cycle were determined in breast tissue samples. In the DMBA group, plasma CA15-3, CEA, VEGF, MMP-9, and NF KB levels were significantly increased compared to the controls, but significant decreases were observed in these parameters except MMP-9 in the treatment groups. It was observed that p53 and Bax expressions significantly increased in both D + P and D + P + T groups compared to the DMBA group, and these findings were supported by Tunel and immunohistochemical findings. Cyclin D1 expressions were found to be significantly decreased only in the D + T group and supported by TUNEL and immunohistochemical findings. Immunohistochemical ER-alpha and Ki-67 immune reactivities were significantly decreased in all treatment groups compared to the DMBA group. Our results showed that combined application of pomegranate extract and tangeretin may be more beneficial in preventing breast cancer development. 0 2020 Elsevier Inc. All rights reserved.
Keywords: Breast cancer model; Tangeretin; Pomegranate extract; Nutraceuticals; Chemoprevention